The relationship of liquidity, financial structure, and profitability on market value through asset management efficiency in sustainable stocks in Thailand - Dankul, Malert; Attarit , Thanapin; Preungvate, Kullapa (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2025)
This research aims to confirm the structure of financial ratios, including liquidity, financial structure, and profitability, and their effect on market value through asset management efficiency in sustainable stocks in Thailand. The study focuses on 149 companies listed on the Stock Exchange of Thailand. Secondary data were collected from the SET SMART database of the Stock Exchange of Thailand and analyzed using structural equation modeling (SEM), with model fit indices used to assess the consistency between the theoretical model and the empirical data. The research results showed that the current ratio (CUR) had an average of 1.9946 and a standard deviation of 1.51495. The debt-to-equity ratio (LEVE) had an average of 196.83 and a standard deviation of 2,000.51. The earnings per share (EPS) had an average of 1.74 and a standard deviation of 3.395. The price-to-earnings ratio (PE) had an average of 31.094 and a standard deviation of 107.909. The dividend payout ratio (DPR) had an average of 0.998% and a standard deviation of 1.255%. The return on equity (ROE) had an average of 11.333% and a standard deviation of 11.684%. The sustainability rating (ESGRATE) had an average of 3.651 and a standard deviation of 0.929. The market value of securities (MARKET) had an average of 83,851.042 million baht and a standard deviation of 168,741.154 million baht. The analysis of the structural model testing the relationships among liquidity, financial structure, and profitability on market value through asset management efficiency-focusing on sustainable stocks in Thailand in the post-COVID-19 context-revealed the following: The coefficient of determination (R²) for the latent endogenous variables showed that the predictive power for ESG rating (ESGRATE) was 0.125, or 12.5%, and for market value (MARKET) was 0.224, or 22.4%. This indicates that the model could explain 22.4% of the variation in market value. In terms of both direct and total effects, the ESG rating (ESGRATE) was significantly influenced by earnings per share (EPS), with a coefficient of 0.329 at the 0.05 significance level. For the market value (MARKET), the direct effects were statistically significant as follows: Current ratio (CUR) = -0.171, Earnings per share (EPS) = 0.224, ESG rating (ESGRATE) = 0.258, Additionally, the results showed: The current ratio had a direct effect on the dependent variable, Earnings per share served as a partial mediator, indicating both direct and indirect influence on market value through ESG performance.